Rancang Bangun Sistem Informasi Terapi Autisme dengan Metode Applied Behaviour Analysis (Studi Kasus: Sekolah Harapan Bunda Surabaya) - Juliana Poernomo Putri; M. J. Dewiyani Sunarto; Tan Amelia (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
A childwith autismhas impairedresulting indelays inmentalageto agechronologically. One of themost important thingsin the process ofhealingchildrenwithautismisaroutinetreatmentthat takes a long time. The therapy that has been usedinthe Harapan BundaSchoolis a therapyusingAppliedBehaviorAnalysis (ABA). In the process oftherapyof autistic childrenaged2 to3years require2.5until3yearsof recording. Without orderly recording, there will be a lot offorgetfulness, bothprograms, therapy and outcomeof therapy. Thenumber of datarecordseach dayof therapythat is used toproducetherapeutic resultsbecome the problematicfortheschool database recordwhich is orderly,neatandaccurate informationis needed inthe process ofmonitoringthe child's developmentto avoiderrorsin decidingthe propertreatmentprogramfor thechildren. Based ona problems survey above, it needs an information system that helpsthe schoolin monitoringchild development. Theproblem of BuildingInformation SystemsAutismtherapyusingthe ABAmethodishow to designandbuild information systems for autismtherapyusingAppliedBehaviorAnalysismethodtofacilitatetheobservingof child development. InformationSystems Design for Autismtherapyusing theABAmethodis a systemthat helpsthe schoolin monitoringchild development. So it canbe a solutionto theproblemin decidingthe appropriate treatmentprogramatHarapan Bunda SchoolofSurabaya. Key words: autism, a programof therapy,ABAtherapy.